IDENTIFIKASI KADAR ALKOHOL DALAM TONER PEMBERSIH WAJAH MENGGUNAKAN GC-FID - Said, Alga; Oileri Tikirik, Wita; Sahrianti, Nini; Tarnoto, Tenny (Politeknik Negeri Ketapang, 2023)
Facial toner is a liquid that is used to freshen the face and clean remaining dirt, used after washing the face with cleansing soap. In addition, facial toner also functions to balance the pH of facial skin which tends to be alkaline due to cleansing soap. However, who would have thought that facial cleansing toner contains alcohol. This research used a total sampling technique carried out at the Stikes Andini Persada Mamuju Laboratory where the population was the same as the number of samples, namely 3 samples, which was carried out in July-October 2023. The conclusion of the research on identifying the ethanol content of facial cleansers circulating in Mamuju City using GC-FID is that based on the results of organoleptic observations of 3 samples, they have a liquid texture, as well as different colors and odors, but they are all the same as the characteristics of alcohol, the results of the observations using reagents, there were 3 samples that were positive for containing alcohol, and the results of testing using gas chromatography (GC-FID) showed that the samples contained alcohol but the levels were below 5%, but sample Y contained 12% alcohol & sample Z contained 15% alcohol. So it is recommended that people be more careful when using facial cleansing toners, especially facial cleansing toners that do not have BPOM permission.